Novel Method for Rapid Determination of Clarithromycin Sensitivity in Helicobacter pylori - Gibson, J. R. (American Society for Microbiology, 1999)
A novel PCR-hybridization assay, performed in single closed capillaries, was developed to detect clarithromycin resistance-associated gene mutations in Helicobacter pylori. Mutations were detected by thermal analysis in 33 of 34 (97%) resistant isolates but not in 66 isolates determined to be sensitive by conventional antibiotic assays. The method was rapid and reproducible, and it reduced PCR product contamination risk.